The effects of nitrogen partial pressure on the microstructure of amorphous carbon nitride films. Issue 180 (4th May 2017) - Jinxin, Wu; Feng, Xu; Peng, Ye; Xiaolong, Tang; Dunwen, Zuo
ABSTRACT: The amorphous carbon nitride (a-CN x ) films with varying nitrogen content were deposited on Si (100) wafers substrates using radio frequency magnetron sputtering (RFMS) from graphite target at different nitrogen partial pressure. The influence of nitrogen partial pressure on the microstructure and phase composition of a-CN x films were researched systematically. The films were characterized by atom force spectroscopy (AFM), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM). AFM results showed cluster structure in a range of tens to hundreds namometers existed on the surface of the films and the surface roughness increased with the increase of nitrogen partial pressure. Ratio of ID /IG increased with the nitrogen partial pressure, while the sp 3 phase content from fitting results of XPS displayed reverse trend. The nanohardness of a-CN x films characterized by nanoindentation test decreased with the increase of nitrogen partial pressure, which consisted with the results of Raman and XPS. Thus high nitrogen partial pressure caused the mechanical properties of a-CN x films decrease.